PENGARUH PENGALAMAN AUDIT INVESTIGASI, BEBAN KERJA, DAN WHISTLEBLOWING SYSTEM TERHADAP KEMAMPUAN AUDITOR DALAM MENDETEKSI KECURANGAN - Alfiana Angesta Poetri, (2022)
This study aims to examine the effect of audit investigative experience, workload, and whistleblowing system to auditor ability to detection fraud. The sample used in this study was an auditor that work at in The Financial and Development Planning Agency (BPKP) DKI Jakarta. Sampling was carried out using a physical and digital questionnaire. Total of sample that has been collected was 46 respondents. The data analysis used in this study was Smart PLS program or Partial Least Square with a significant level of 5%. The result of this study indicate that (1) Audit Investigative Experience has a significant effect on Auditor's Ability to Detection Fraud, (2) Workload has no effect on Auditor's Ability to Detection Fraud, (3) Whistleblowing System has a significant effect on Auditor's Ability to Detection Fraud